To what extent are teaching assistants really managed?: 'I was thrown in the deep end, really; I just had to more or less get on with it'. (27th May 2017) - Basford, Elisabet; Butt, Graham; Newton, Richard
ABSTRACT: The main aim of this research was to secure a better understanding of how local authorities (LAs), senior leadership teams (SLTs) and teachers in state schools perceive their responsibilities for the deployment, leadership and management of teaching assistants (TAs). Current research in the field – some of which has been highly influential on policy – has largely focused on aspects of TA performance and pupil attainment. Importantly, we have chosen to investigate how TAs and SLTs themselves describe their experiences of management. TAs, teachers, senior leaders in primary schools and LA advisors, across two LAs, were surveyed. Based on 55 questionnaire responses, 23 interviews and 2 focus groups we found evidence of a dislocation of management priorities for effective TA deployment. What emerged was a strong sense of 'otherness' felt by many TAs, who believed themselves to be dissociated from their own management. We conclude that TAs make up a workforce that appears to be closely managed but which is in fact often poorly led, resulting in feelings of detachment.